Concurrent challenges in practical operations and modeling of geological carbon-dioxide sequestration: Review of the Gorgon project and FluidFlower benchmark study - Ruud Weijermars (Energy Strategy Reviews)
This study aims to serve as a reality check on whether the present-day (1) technology readiness level, and (2) storage capacity modeling, are adequate to claim that geological carbon-dioxide sequestration (GCS) projects are on a trajectory to help save the world from becoming a boiling greenhouse. The storage of CO2 in subsurface formations is technically feasible, but serious challenges still arise when large quantities of CO2 are injected. For example, important lessons can be gleaned from the world's largest CO2-sequestration project at the Gorgon Field (Australia), which has run into a series of technical setbacks and now is over a decade behind schedule. Similarly, modeling of CO2-fluid migration in the subsurface, which is at the basis of any practical GCS-project design-solution, remains challenging, as appears from careful analysis of a recent benchmark study effort by nine of the world's leading modeling groups. The limited transferability of FluidFlower modeling benchmark results and the technical challenges encountered in the Gorgon GCS project are highlighted. From the analysis, concurrent bottlenecks in technical operations and modeling capacity are identified, and suggestions are made for possible pathways to overcome these challenges.